Design Response Spectra Based on Earthquake Hazard Maps and Specific Soil Properties at Indonesian Ports According to SNI 1726 2019 - Christino Boyke Surya Permana (Jurnal Teknik Sipil, 2021)
Indonesia has a new seismic code, namely SNI 1726 2019 (SNI 2019). It is developed based on the 2017 Indonesian Earthquake Source, Hazard Maps, and ASCE 7-16. This paper is intended to explain the procedure for calculating response spectrum according to SNI 1726 2019, at ten ports located in Indonesia. The results are then verified with the software RSA2019. Furthermore, it will be compared to SNI 1726 2012 (SNI 2012) to see the difference in spectral acceleration value (Sa). The result presents that the ports located in Sorong and Banggai have the highest Sa, whereas the port in Banjarmasin has the smallest value. Port in Surabaya and Tuban have nearly the same Sa due to their close location, while Banyuwangi has a Sa value slightly above them. The ports in Padang, Lampung, and Penajam must use a specific site response analysis to determine the design response spectra, which is not discussed in this paper. The comparison with SNI 2012 shows that the response spectra of SNI 2019 have a higher Sa than SNI 2012. However, in some areas such as Tuban and Sorong, the Sa of SNI 2012 at 0.1 to 0.6 s period are larger than SNI 2019.